ANALISIS KELAYAKAN INVESTASI KERTAS KEMASAN PANGAN ANTI MIKROBA BERBAHAN BAKU KULIT BIJI KAKAO - Yusriadin Yusriadin; Anugrah Hidayat (Jurusan Penyuluhan Pertanian FP UHO, 2025)
This study aims to analyze the feasibility of investing in antimicrobial food packaging paper products made from cocoa bean shells. The research was conducted at the production facility of CV. Sultan Agro-Maritim Industri, located in Kendari City. The location was chosen purposively because CV. Sultan Agro-Maritim Industri is the only industry partner for the UHO lecturer team conducting trials on the production of antimicrobial. The data used in the study consisted of primary data obtained through interviews with respondents from the cocoa processing industry, as well as secondary data relevant to the research topic. Data collection techniques included in-depth interviews with key respondents and literature studies. The data analysis applied was investment feasibility analysis. The results of the study indicate that the production of antimicrobial food packaging paper made from cocoa bean shells is feasible to develop, with a Net Present Value (NPV) of IDR 17,001,698, a Net Benefit Cost Ratio (Net B/C) of 1.47, Internal Rate of Return (IRR) of 73.00%, and Payback Period (PP) of 1.79 years.